RESPON KIAI KOTA KEDIRI TERHADAP PERBEDAAN ALASAN FATWA MUI PUSAT DAN MUI JATIM DALAM HUKUM VAKSIN ASTRAZENECA - Nilna Fauza (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2022)
Some people are that, the use of vaccines is halal, but others are the opposite. Related to this, the Central MUI responded to public anxiety by issuing 2 fatwas, namely the fatwa for the law on the Sinovac vaccine and the Astrazeneca vaccine. As for the Sinovac vaccine, based on fatwa Number: 02 of 2021, it is stated that the Covid-19 Vaccine Product from Sinovac Life Sciences Co. Ltd. China And PT. Bio Farma (Persero) is lawful and holy. While the astrazeneca vaccine is based on Fatwa No. 14 of 2021 concerning the Law on the Use of 19 Astrazeneca vaccines, the law is haram. The existence of taking advantage of pig trypsin in the vaccine production process became the basis for determining the haram fatwa. However, its use is permitted for emergency reasons. Unlike the Central MUI, the East Java MUI stated otherwise. In the meeting of the East Java MUI Fatwa Commission on March 21, 2021, it was determined that the vaccine developed by the University of Oxford and AstraZeneca Plc was halalan thayyiban or halal and good. This resulted in a dualism of fatwa, namely the fatwa issued by the central MUI and the East Java MUI, even though the ending was both applicable. Therefore, the researcher considers it very important and fundamental to examine the responses of the kiai in the city of Kediri, especially the kiai of the Islamic boarding school Lirboyo and Al Falah Ploso to the fatwa of the central MUI and the East Java MUI regarding the Astrazeneca vaccine law. This paper aims to (1) examine the responses of the kiai of the city of Kediri to the differences in the fatwas of the central MUI and the MUI of East Java in the use of the Astrazeneca vaccine, (2) assess the response of the kiai of the city of Kediri on the understanding and willingness of the public to participate in the government's vaccine program